Echocardiographic evaluation of patients with sickle cell disease. A study based on Etendar Cohort. (25th November 2020) - d'Humieres, T; Savale, L; Inamo, J; Damy, T; Lionnet, F; Loko, G; Derumeaux, G; Humbert, M; Bartolucci, P
Abstract: Background: Echocardiography is the main non-invasive screening tool for pulmonary hypertension (PH) in Sickle Cell Disease (SCD), but relies mostly on the tricuspid regurgitation velocity (TRV) assessment, without distinction between pre and postcapillary patterns. Purpose: Using Etendard Cohort data, the aim of this study was to refine echocardiographic assessment of PH in SCD patients. Methods: The French Etendard Study is a prospective cohort initially designed to assess the prevalence of PH among 398 SCD participants. We analyzed echocardiography data of the 96 Etendard patients who underwent Right Heart Catheterization (RCH), because of a TRV≥2.5m/s, and compared them to invasive haemodynamic measurements. Based on RHC results, patients were classified as follows: Absence of pulmonary hypertension if mean pulmonary arterial pressure (mPAP) was <25mmHg. Precapillary PH if mPAP≥25mmHg and pulmonary-capillary wedge pressure (PCWP) ≤15mmHg. Postcapillary PH if mPAP≥25mmHg and PCWP >15mmHg. Results: PH was found in 24/96 patients with 11 precapillary and 13 postcapillary. In addition to TRV, multivariate analysis identified indexed left atrial volume (LAVind) and lateral E' wave velocity (E'lat) as independent echocardiographic predictors of PH (OR=1.06 and 0.6 respectively, p<0.01). LAVind and E'lat showed good correlation with mPAP (R=0.51 and R=0.40 respectively and p<10–3 for both) and had good accuracy to predict PH with an optimal cut-off of 48ml/m 2 for LAVind (AUC=0.78, Se=81% and Sp=75%) and 12cm/s for E'lat (AUC=0.8, Se=72% and Sp=79). Using the association of a TRV≥3m/s or a TRV [2.5; 2.9] m/s with LAVind>48ml/m 2 and E'lat<12cm/s, we could predict PH with a PPV of 68% and NPV of 90%. Moreover, comparing echocardiography data of pre and post-capillary PH patients, we observed that Pulmonary acceleration time (PAcT) was different in the two groups (104±22ms vs. 160±21ms, p<0.001) with an excellent accuracy for the differentiation of both phenotypes (AUC=0.95, optimal cut-off=115ms, Se=100% and Sp=78%). PAcT correlated with pulmonary vascular resistance (PVR) assessed by RHC (R=0.34, p=0.001) but not with mPAP (R=0.1, p=0.2) and a PAcT>115ms ruled out pre-capillary PH with a NPV of 97%. Conclusion: Echocardiography can accurately estimates the probability of PH in SCD patients with an integrated approach using TRV, LAVind and E'lat. In addition, among patients with suspected PH, measuring PAcT as a PVR surrogate allows a good differentiation between pre and post-capillary phenotypes. We propose a new echocardiographic algorithm for the diagnosis of PH in SCD that could be a true assistance in referring patients for RHC. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Funded by the French Ministry of Health and Assistance Publique–Hôpitaux de Paris